Kekerabatan Genetik Populasi Bengkuang Pachyrhizus erosus Berdasarkan Karakter Morfologi Bunga dan Daun - Karuniawan, Agung; Wicaksana, Noladhi (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2006)
Yam bean Pachyrhizus erosus is widely cultivated in Central America, Africa, Asia and Pacific. The objective of the research was to analyse genetic relationships of yam bean originated from Indonesia compared to its ancestor species from Mexico and Guatemala. Fourty three yam beans consisted of 35 genotypes from Indonesia and 8 introduced genotypes from Mexico and Guatemala were planted under complete block design with two replications. Fourteen significant different traits from 25 morphological leaf and flower properties traits have been used to analyse the genetic relationships. Results showed that yam beans from Sumatra differed from its relatives from the rest regions of Indonesia. Yam bean populations originated from Indonesia are closely related to its ancestor species from Mexico and Guatemala. Key words : Yam bean, Pachyrhizus erosus, genetic relationships